Approximations to linear Klein–Gordon Equations using Haar wavelet - Sana Ikram (Elsevier, 2021)
In this research article, two Haar wavelet collocation methods (HWCMs) (namely one dimensional HWCM and two dimensional HWCM) are adapted to approximate linear homogeneous and linear non-homogeneous Klein–Gordon equations. The results obtained from both methods are compared with exact solutions. Moreover, both of the methods are also compared together, that indicates much better performance of two dimensional Haar wavelet collocation method (2D HWCM) in a small number of collocation points.